2015
DOI: 10.1002/adfm.201404540
|View full text |Cite
|
Sign up to set email alerts
|

High Bulk Electron Mobility Diketopyrrolopyrrole Copolymers with Perfluorothiophene

Abstract: The question of designing high electron mobility polymers by increasing the planarization using diffusive nonbonding heteroatom interactions in diketopyrrolopyrrole polymers is addressed in this. For this, three different diketopyrrolo[3,4‐c]pyrrole (DPP) derivatives with thienyl‐, 2‐pyridinyl‐, and phenyl‐flanked cores are copolymerized with an electron‐rich thiophene unit as well as an electron‐deficient 3,4‐difluorothiophene unit as comonomer to obtain diverse polymeric DPPs which vary systematically in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 53 publications
12
111
0
Order By: Relevance
“…These two features could be of interest to design new organic n-type semiconducting materials. Along these lines, Jo and Thelakkat groups have shown that Diketopyrrolopyrrole-based polymers using fluorine-flanked π-linkers between two adjacent DPP moieties lead to higher electron mobilities in comparison to non-fluorinated ones [29,94]. Interestingly, Jo and co-workers have shown, on the DPPPhF n copolymer series (Figure 21), that increasing the number of fluorine substitutions does not only impact the LUMO level, which decreases slightly, but it also modifies the polymer chain orientation in thin films, with a face-on orientation becoming more favorable.…”
Section: N-type Fluorinated Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…These two features could be of interest to design new organic n-type semiconducting materials. Along these lines, Jo and Thelakkat groups have shown that Diketopyrrolopyrrole-based polymers using fluorine-flanked π-linkers between two adjacent DPP moieties lead to higher electron mobilities in comparison to non-fluorinated ones [29,94]. Interestingly, Jo and co-workers have shown, on the DPPPhF n copolymer series (Figure 21), that increasing the number of fluorine substitutions does not only impact the LUMO level, which decreases slightly, but it also modifies the polymer chain orientation in thin films, with a face-on orientation becoming more favorable.…”
Section: N-type Fluorinated Polymersmentioning
confidence: 99%
“…For instance, if we consider two of the most common building blocks in the conjugated polymer field, namely the thiophene electron-donating group [26][27][28][29][30][31][32] and the 2,1,3-benzothiadiazole Possible physical mechanisms that may contribute to the remarkable increase in performances after backbone fluorination of different chemical systems have already been discussed in the literature. However, due to the large variety of molecular systems investigated so far and due to the complexity of the physics underlying the photovoltaic effect in organic BHJ devices, a general understanding of the impact of fluorination on the device performances is still lacking.…”
Section: Synthesis Of Fluorinated Conjugated Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…These preferential alignments directly correlate with the charge transport properties as measured in space charge limited diodes. [100][101][102][103] …”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%